The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/oby.21759
|View full text |Cite
|
Sign up to set email alerts
|

H. Pylori as a predictor of marginal ulceration: A nationwide analysis

Abstract: H. pylori is an independent predictor of marginal ulceration using a large national database. Preoperative testing for and eradication of H. pylori prior to bariatric surgery may be an important preventive measure to reduce the incidence of ulcer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…(2013*). Two recent studies illustrate a relationship of Helicobacter pylori with the occurrence of marginal ulcers postoperatively . Specifically, Mocanu et al found a 10‐fold increase in the rate of this complication in H. pylori –positive versus –negative patients after undergoing RYGB.…”
Section: Executive Summarymentioning
confidence: 99%
“…(2013*). Two recent studies illustrate a relationship of Helicobacter pylori with the occurrence of marginal ulcers postoperatively . Specifically, Mocanu et al found a 10‐fold increase in the rate of this complication in H. pylori –positive versus –negative patients after undergoing RYGB.…”
Section: Executive Summarymentioning
confidence: 99%
“…[38]. Multivariable analysis of a registry cohort found H. pylori status to be the most important independent predictor of marginal ulceration in patients undergoing RYGB, but it had little impact on the outcome of other bariatric operations [39]. Indirectness of the evidence and imprecision of effect estimates were major parameters to judge the quality of evidence, which was very low across outcomes (Supplementary Table S2).…”
Section: Justificationmentioning
confidence: 99%
“…Based on the results, the authors advise routine H. pylori eradication before bariatric surgeries . These results were confirmed in a large retrospective cohort study, in which 3.9% marginal ulceration was detected and associated in one‐third of the cases with a H. pylori infection. The H. pylori infection was the strongest independent predictor of marginal ulceration, suggesting routine preventive eradication therapy to lower the ulceration incidence …”
Section: Bariatric Surgerymentioning
confidence: 73%
“…The H. pylori infection was the strongest independent predictor of marginal ulceration, suggesting routine preventive eradication therapy to lower the ulceration incidence. 36 Controversial results in the same field were obtained by Wolter et al 37 who compared endoscopic findings to preoperative risk factors and postoperative complications. Out of 801 patients, only 3.7% presented a H. pylori infection.…”
Section: Bariatric Surgerymentioning
confidence: 99%